2015
DOI: 10.1039/c5nr03157e
|View full text |Cite
|
Sign up to set email alerts
|

New insight on optical and magnetic Fe3O4 nanoclusters promising for near infrared theranostic applications

Abstract: Extensive efforts have been devoted to the development of a new biophotonic system using near infrared (NIR) nano-agents for non-invasive cancer diagnosis and therapy. Here, we developed a simple synthesis reaction of ligands, hydrazine, and iron(ii) chloride to fabricate Fe3O4 cluster-structured nanoparticles (CNPs) with interesting NIR photonics and high magnetization (Ms: 98.3 emu g(-1) and proton relaxivity r2: 234.6 mM(-1) s(-1)). These Fe3O4 CNPs exhibited optical absorption and reflection over all wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…These Fe 3 O 4 CNPs exhibited interesting NIR photonics for magnetomotive optical coherence tomography cellular imaging at 860 nm (~10 mW) combined with enhanced PTT using Fe 3 O 4 CNPs and a magnetic field at 1064 nm (380 mW cm − 2 ). 76 …”
Section: Fe 3 O 4 Nanostructuresmentioning
confidence: 99%
“…These Fe 3 O 4 CNPs exhibited interesting NIR photonics for magnetomotive optical coherence tomography cellular imaging at 860 nm (~10 mW) combined with enhanced PTT using Fe 3 O 4 CNPs and a magnetic field at 1064 nm (380 mW cm − 2 ). 76 …”
Section: Fe 3 O 4 Nanostructuresmentioning
confidence: 99%
“…Superparamagnetic iron oxides (SPIOs) are typically desired because they maintain strong magnetic susceptibility while lacking remanent magnetization. Thus, MMOCT contrast agents tend to have MIO cores between ~10-50nm, although larger particle clusters [27] or novel ferrofluid-filled microspheres [28] have been developed for certain applications.…”
Section: Magnetomotive Oct: Theory and Practicementioning
confidence: 99%
“…Huang et al (2015) report a novel clustered magnetic nanoparticle with both light scattering properties at 860 nm for OCT imaging, and absorbing properties at 1064 nm for photothermal therapy [27]. Thus, cancer cells were shown to be both imaged and subjected to hyperthermia by the same particles.…”
Section: Magnetomotive Oct Experimentsmentioning
confidence: 99%
“…Apart from these uses in industrial, energy, and magnetic fields, few optical investigations have studied several distinct kinds of iron oxide nanomaterials, thus limiting the development of these materials as optical sensors, for microscopic imaging, and in photon‐to‐thermal therapy in photomedicine . Recently, our group and other researchers reported that surface‐modified and/or highly crystalline Fe 3 O 4 nanoparticles exhibited strong near‐infrared (NIR) absorption for efficient NIR‐to‐thermal ablation of cancerous cells at a low power within 10 min of irradiation. These unique NIR absorption properties of iron oxide–based nanomaterials were recently used in applications as fluorescent probes, polymerase chain reaction (PCR) photoheaters, and repeatable photothermal scaffolds …”
Section: Introductionmentioning
confidence: 99%